Case Report: Progressive disease of BRCA2-mutant colon adenocarcinoma following talazoparib therapy - Polyanskaya, Elizaveta; Lebedeva, Alexandra; Kuznetsova, Olesya; Belova, Ekaterina; Kavun, Alexandra; Ivanov, Maxim; Fedyanin, Mikhail; Tryakin, Alexey; Mileyko, Vladislav; Nosov, Dmitry (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is currently one of the most common tumor types diagnosed worldwide. In the early stages, the disease responds well to surgical and chemotherapeutic treatment, but in the later stages when therapeutic options are exhausted, comprehensive genomic profiling can guide further treatment decisions. We present the case of a 46-year-old man of Ashkenazi Jewish ancestry who was diagnosed with KRAS-mutated metastatic colorectal cancer. After surgery and progression on standard FOLFOX/FOLFIRI + bevacizumab therapy, as well as on Trifluridine/Tipiracil, comprehensive genomic profiling was performed with the hope of expanding therapeutic options. Following comprehensive tumor molecular profiling via NGS, a discussion of the case was discussed at the local molecular tumor board in order to determine further treatment strategy. An activating variant of KRAS and PIK3CA, FLT3 and SRC amplification and damaging TP53 and APC variants were discarded by MTB as potential targetable biomarkers. The BRCA2 p.S1415fs*4 founder frameshift variant was of interest and the patient was included in the clinical trial investigating the efficacy of a PARP inhibitor talazoparib. Unfortunately, the disease progression was detected within one month of talazoparib treatment and the patient died during the 8th cycle of FOLFIRI + bevacizumab therapy rechallenge.